The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.resuscitation.2016.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic effect of repeated adrenaline (epinephrine) doses during cardiopulmonary resuscitation in the cath lab setting: A randomised porcine study

Abstract: Repetitive intravenous adrenaline doses increased ABP's and to some extent also CePP, but significantly decreased organ and brain perfusion. The institutional protocol number: Malmö/Lund Committee for Animal Experiment Ethics, approval reference number: M 192-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 36 publications
1
25
1
1
Order By: Relevance
“…While epinephrine increases systemic arterial blood pressure, there are conflicting experimental results regarding its effect on cerebral blood flow (CBF) and cerebral tissue oxygenation. Specifically, animal studies have demonstrated both increases [13][14][15][16][17] and decreases [18][19][20][21] in various measurements of CBF following epinephrine administration during CPR. Maintaining CBF during CPR is an important physiologic target to minimize potentially devastating effects of cerebral hypoperfusion during this vulnerable period.…”
Section: Introductionmentioning
confidence: 99%
“…While epinephrine increases systemic arterial blood pressure, there are conflicting experimental results regarding its effect on cerebral blood flow (CBF) and cerebral tissue oxygenation. Specifically, animal studies have demonstrated both increases [13][14][15][16][17] and decreases [18][19][20][21] in various measurements of CBF following epinephrine administration during CPR. Maintaining CBF during CPR is an important physiologic target to minimize potentially devastating effects of cerebral hypoperfusion during this vulnerable period.…”
Section: Introductionmentioning
confidence: 99%
“…They found that administration of 0.04 mg/kg of epinephrine during CPR significantly decreased carotid blood flow and EtCO 2 and discussed potential increase in macrocirculation and ventilation-perfusion mismatch when epinephrine was given as the most likely explanation of their findings. Similarly, Martin et al 31 and Hardig et al 32 examined the effects of epinephrine dosing on EtCO 2 in dog and swine models of cardiac arrest. Martin et al found that using 0.045 mg/kg IV of epinephrine resulted in significant decrease of EtCO 2 , while Hardig et al found that using 0.02 to 0.03 mg/kg of epinephrine resulted in a significant reduction in EtCO 2 when compared with normal saline.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors suggest that patients who require the administration of adrenaline during CPR have a higher chance of achieving a return of spontaneous circulation, which does not necessarily influence long-term neurological functioning (e.g., according to the CPC scale) or the risk of long-term mortality [18, 19]. Repeating adrenaline doses after the cessation of circulation impairs microcirculatory perfusion in the central nervous system and exacerbates already existing metabolic disturbances [20]. This has been reflected in the current guidelines for resuscitation: their authors advise caution when considering the administration of adrenaline [1].…”
Section: Discussionmentioning
confidence: 99%